The role of police occupational culture on officers’ job satisfaction and work motivation - Demirkol, Ismail Cenk (International journal of comparative and applied criminal justice, 2021)
The aim of this paper is to investigate the effects of police occupational culture on police officers’ job satisfaction and motivation in Turkey. Drawing data from a survey of 1970 Turkish National police officers, six dimensions of police occupational culture – including authoritarianism, alienation, social cohesion and loyalty, cynicism towards the public, and autonomy – were identified to assess their impact on motivation and job satisfaction of officers. The findings suggest that social cohesion, loyalty, and autonomy were significant and positive predictors of police officers’ job satisfaction but alienation and cynicism were found to have a negative relationship with job satisfaction. Regarding motivation, while alienation and authoritarianism had a negative effect on police officers’ work motivation, social cohesion was positively related to motivation. These mixed findings suggest that there is a wide variation in how various dimensions of police occupational culture influence officers’ job satisfaction and work motivation.